TGFβ1‑induced epithelial‑mesenchymal transition is associated with stathmin downregulation and increased microtubule stability in bronchial epithelial cells - Mohamad Hasan, Nur Amilia Hanie; Lee, Yu Zhao; Tham, Chau Ling; Ahmad Israf, Daud; Jambari, Nuzul Noorahya; Harith, Hanis Hazeera (Spandidos Publications, 2025)
Epithelial-mesenchymal transition (EMT) is a pathophysiological process contributing to bronchial remodeling in airway diseases such as chronic obstructive pulmonary disorder. EMT in several types of cancer involves dysregulated microtubule dynamics. Stathmin, a microtubule destabilizer, is highly expressed in different types of cancer, and is associated with decreased microtubule stability and enhanced migratory capability. The present study examined the relationship between stathmin expression and microtubule stability in bronchial EMT using an in vitro model. Primary normal human bronchial epithelial (NHBE) cells and the BEAS‑2B bronchial epithelial cell line were induced with TGFβ1 for 48 or 72 h to activate EMT, with or without the TGFβ1 inhibitor, SB431542. TGFβ1‑induced cells exhibited significantly reduced E‑cadherin (epithelial marker) and increased vimentin (mesenchymal marker) expression, which was inhibited by SB431542. TGFβ1-mediated EMT was associated with reduced stathmin levels and increased microtubule stability (indicated by acetylated-α-tubulin) in BEAS‑2B and NHBE cells. However, TGFβ1‑induced EMT did not significantly enhance cell migration, potentially due to stabilized microtubules. By contrast, 10% fetal bovine serum induced a more robust EMT phenotype, accompanied by increased stathmin expression, reduced microtubule stability and enhanced cell migration. The present study highlights the potential role of stathmin in modulating microtubule dynamics during bronchial remodeling and hypothesizes its involvement in the transition from partial to full EMT, depending on the EMT‑inducing stimulus.